Genetic modification of scAAV‐equine‐BMP‐2 transduced bone‐marrow‐derived mesenchymal stem cells before and after cryopreservation: An "off‐the‐shelf" option for fracture repair. Issue 6 (21st February 2019) - Ball, Alyssa N.; Phillips, Jennifer N.; McIlwraith, C. Wayne; Kawcak, Christopher E.; Samulski, Richard J.; Goodrich, Laurie R.
ABSTRACT: Optimizing the environment of complex bone healing and improving treatment of catastrophic bone fractures and segmental bone defects remains an unmet clinical need both human and equine veterinary medical orthopaedics. The objective of this study was to determine whether scAAV‐equine‐BMP‐2 transduced cells would induce osteogenesis in equine bone marrow derived mesenchymal stem cells (BMDMSCs) in vitro, and if these cells could be cryopreserved in an effort to osteogenically prime them as an "off‐the‐shelf" gene therapeutic approach for fracture repair. Our study found that transgene expression is altered by cell expansion, as would be expected by a transduction resulting in episomal transgene expression, and that osteoinductive levels could still be achieved 5 days after recovery, and protein expression would continue up to 14 days after transduction. This is the first evidence that cryopreservation of genetically modified BMDMSCs would not alter the osteoinductive potential or clinical use of allogeneic donor cells in cases of equine fracture repair. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:1310–1317, 2019.